PENGARUH KETERLIBATAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PASAR MODERN PASIR PENGARAIAN KABUPATEN ROKAN HULU - muliana, yuna (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
The research was conducted on Modern Market Pasir Pengaraian Rokan Hulu. This research aims to determined how the effects of job involvement and job satisfaction on turnover intention in Modern Market Pasir Pengaraian Rokan Hulu. A population of 68 people. The number of samples in this research were 40 respondents. The sampling technique used in this research by random sampling. Collecting data using questioner. Once the data is collected and entered into the table, calculated the percentage of respondents to see the highest and lowest response, then analyzed using SPSS version 18.00. Based on the testing that was done, regression test simultaneously (F) showed that the independent variables studied (work engagement and job satisfaction) together (Simultaneous) have a significant effect on the dependent variable (Turnover Intention). Results of the testing that has been done, partial regression test (t) indicates that each of the independent variables studied (work engagement and job satisfaction) have a significant effect on the dependent variable (Turnover Intention). Furthermore, based on the above calculation that value obtained by the coefficient of determination (R2) of 0.207. This shows that the work engagement and job satisfaction impact of 20.7% on turnover intention in Modern Market Pasir Pengaraian Rokan Hulu.